On the issue of the activities of cultural institutions of Chechen-Ingushetia in 40-kh – early 60-kh XX century. - Olga Semenova (Кавказология)
The article explores various facets of cultural life, focusing on the activities of cultural institutions in Chechen-Ingushetia during the 1940s to the 1960s. Following the deportation of the indigenous population to Kazakhstan and Kyrgyzstan, individuals from different regions of the USSR were relocated to fill the void. The objective of this study is to illustrate the role of culturalinstitutions during that time, highlighting their significance for the Chechen population, as well as their contribution in mitigating the socio-political crisis that ensued as a result of the USSR leadership's decision to deport certain ethnic groups. The Soviet government provided the resettled individuals with familiar cultural establishments such as theaters, clubs, libraries, and schools. Consequently, this research explores the distinct characteristics of these institutions, analyzes their level of development, and determines their importance in facilitating the return of Chechens and Ingush people to their homeland. Furthermore, new materials and sources pertaining to this research topic have been introduced. The study incorporates materials from the periodical press of that era, specifically the newspaper Grozny Rabochy. Based on the reviewed material, it can be concluded that the shared socio-cultural space, values, and ideals of society possess the capacity to tackle even the most challenging problems, foster unity among people, and aid in overcoming arduous socio-political crises.